AB0440 Serum Uric Acid Levels Predict New Renal Damage in Systemic Lupus Erythematosus Patients. (15th July 2016) - Reátegui-Sokolova, C.; Ugarte-Gil, M.; Gamboa-Cardenas, R.; Zevallos, F.; Cucho-Venegas, J.M.; Alfaro-Lozano, J.; Medina, M.; Rodriguez-Bellido, Z.; Pastor-Asurza, C.; Perich-Campos, R.
Abstract : Background: Renal involvement is one of the most serious and frequent manifestations of systemic lupus erythematosus (SLE) and is associated with increased morbidity and mortality. Uric acid levels have been associated with the progression to subsequent end-stage renal disease in patients with chronic kidney disease (1) . Uric acid has been reported to be associated with new onset lupus nephritis (2) ; however, the association between uric acid levels and renal damage has not been reported in SLE patients. Objectives: To determine whether uric acid level predicts new renal damage in SLE patients after adjusting for known confounding factors. Methods: This longitudinal study was conducted in consecutive SLE patients seen in our Rheumatology Department since 2012. Every patient had a baseline visit; follow-up visits were conducted every 6 months. For the purpose of this study, patients with at least two visits were included. Patients with end-stage renal disease (regardless of dialysis or transplantion) were excluded for this analysis. Renal damage was ascertained using the SLICC/ACR damage index (SDI). Uric acid was measured in mg/dl. Survival analyses using univariable and multivariable Cox-regression models were performed to determine the risk of new renal damage. The multivariable model was adjusted for age at diagnosis, gender, disease duration, socioeconomic status, SLEDAI, SDI, serum creatinine, use of prednisone, antimalarials and immunosuppressive drugs at baseline. Results: One hundred and eighty-six patients were evaluated; their mean (SD) age at diagnosis was 36.8 (13.7) years; nearly all patients were Mestizo. Disease duration was 7.7 (6.8) years. Time of follow-up was 2.3 (1.1) years. At baseline, uric acid levels were 4.5 (1.3) mg/dl, the SLEDAI was 5.2 (4.3) and the SDI 0.8 (1.1). Sixteen (8.6%) patients had one point in renal domain at baseline and 2 (1.1%) had two. During the follow-up 16 (8.6%) patients developed at least one new point in the renal domain of the SDI. In univariable and multivariable analyses uric acid level at baseline predicted the development of new renal damage [HR: 2.24 (1.50–3.34), p<0.001; HR: 3.21 (1.39–7.42), p=0.006; respectively]. Conclusions: Higher uric acid levels predict the development of new renal damage in SLE patients even after adjusting for other well-known risk factors. References: Uchida S, Chang WX, Ota T, Tamura Y, Shiraishi T, Kumagai T, et al. (2015) Targeting Uric Acid and the Inhibition of Progression to End-Stage Renal Disease – A Propensity Score Analysis. PLoS ONE 10(12): e0145506. Zaixing Yang, Yan Liang, Weihua Xi, Ye Zhu, Chang Li, Renqian Zhong (2011) Association of serum uric acid with lupus nephritis in systemic lupus erythematosus. Rheumatol Int (2011) 31:743–748 Disclosure of Interest: None declared